A importânica dos recursos de multimeios na Biblioteca Arthur Viana: desafios ao atendimento ao usuário - PASCOAL, Ricardo Silva (2019)
The choice of theme "The Importance of Multimedia Resources In the Arthur Viana Library: Challenges to the service to users", started from the interest as user, volunteer, trainee and extensionist of the Foundation. The multimedia present importance, because it forms new possibilities of readings, in the process of the dissemination of the information. Multimedia should be seen as allies as full of reading. The research is exploratory and qualitative, which are divided into the following chapters. The first addresses the issue of multimedia, its purposes and benefits, along with the selection process, acquisition and dissemination and the challenges to user service and the value of Public Libraries. The second chapter will address the Arthur Viana Library, will show its history and the sections it offers to the public. The third is the application of the methodology, which will apply questionnaires of qualitative oral interviews with the employees of the Fonoteca, Brinquedoteca and the Coordination through the transcription of the recording, whose collection is the interviews and the analysis of the transcription of the interviews. The fourth chapter reflects the experiences as a volunteer, trainee and extensionist, which will reveal the importance of the Arthur Viana Library together with the multimedia